ANALYSIS OF MATHEMATICAL MODELS OF INVESTMENT STRATEGIES IN THE UNIVERSITY ON CYBER SECURITY SYSTEMS - B. B. Akhmetov; V. A. Lakhno; A. B. Adranova; L. M. Kydyralina; L. D. Pliska (Scientific Journal of Pedagogy and Economics, 2020)
The article provides an overview and analysis of mathematical models for choosing investment strategies in cybersecurity systems of informatization objects (IO) as a particular example of educational information systems (IS). The purpose of the work is the analysis and comparison of known and new investment models for the IO protection. It is shown that previous researches have often purely economic nature and do not take into account the trends relating to the introduction of innovative information technologies in the control and decision-making procedures of the IO cybersecurity tasks. It is shown that the optimal value of resources allocated for the IO protection and cybersecurity depends not only on the vulnerabilities of IS, but also on the cost of information should be protected. All this makes it relevant to develop new models for the decision-making support on the IO protection and cybersecurity investment. The task, in particular, can be solved through the use of new information technologies and computer-based decision support systems (DSS). As a variant, it was proposed to use as a basic mathematical model for DSS the models based on game theory.